High-residual-magnetism high-coercive-force magnet and preparation method thereof

By forming a heavy rare earth shell in the neodymium iron boron system magnet and regulating the generation and distribution of grain boundary phases by using a three-stage tempering process, the coercive force and residual magnetism of the neodymium iron boron sintered magnet in the prior art is solved, and the effect of high residual magnetism and high coercive force is achieved.

CN119763967AActive Publication Date: 2025-04-04NINGBO KONIT IND +4

Patent Information

Application Number
CN202411973150.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-04
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

While improving the coercive force and residual magnetism of the neodymium iron boron sintered magnet, it is difficult to maintain the consistency of the coercive force and residual magnetism of the rare earth permanent magnet diffusion alloy, and the reserves of heavy rare earth elements are scarce and expensive.

Method used

By forming a heavy rare earth shell in the neodymium iron boron system magnet, and using a three-stage tempering process to regulate the generation and distribution of grain boundary phases, reasonably adjust the ratio of high-melting point metal elements to Ga elements, and optimize the addition ratio of Cu elements to improve the residual magnetism and coercivity of the magnet.

Benefits of technology

The neodymium-ferrobor-based magnet with high residual magnetism and high coercivity is achieved, which avoids the excessive use of heavy rare earth elements, reduces production costs, and improves the temperature stability of the magnet.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119763967A_ABST
    Figure CN119763967A_ABST
Patent Text Reader

Abstract

The invention discloses a neodymium-iron-boron magnet, the neodymium-iron-boron magnet comprises R2T14B main phase grains and a grain boundary phase, a heavy rare earth shell layer is arranged on the surface layer of the R2T14B main phase grains in the area, 0.1-100 microns away from the surface of the magnet, of the neodymium-iron-boron magnet, the neodymium-iron-boron magnet comprises the following components: 28-32 wt% of R, 0.85-0.94 wt% of B, 0.4-2 wt% of Co, 0.1-0.8 wt% of Cu, 0.1-0.3 wt% of Ga, 0.05-0.5 wt% of Al and 0.4-1.0 wt% of M1, M1 is selected from one or two of Ti, Zr, Nb, W and V, and 63-69 wt% of Fe; wherein R is a rare earth element and at least comprises PrNd and RH, and RH is a heavy rare earth element and is selected from one or two of Dy and Tb; wherein the area of all grain boundary phases in the cross section of the neodymium-iron-boron magnet, which is 0.1-100 microns away from the surface of the magnet, accounts for 5.2-7.5% of the total area of the cross section.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of magnetic materials, and more specifically, to a high remanence and high coercivity magnet and a preparation method thereof. Background Art

[0002] Since its advent, rare earth magnetic materials have been widely used in energy, transportation, machinery, medical appliances and other industries due to their good magnetic properties, and their products also involve many fields of the national economy. As a rare earth magnetic material, NdFeB sintered magnet is one of the most important permanent magnets. Since many applications of NdFeB sintered magnets are in high temperature environments, they are required to have not only high remanence but also high coercivity. Among them, coercivity is the main parameter of permanent magnetic materials. The higher the coercivity, the stronger its anti-demagnetization ability. When applied, not only is the coercivity of NdFeB sintered magnets required to be as high as possible, but it is also required to have good temperature stability so that it can work under higher temperature conditions.

[0003] Common methods for improving the coercivity of NdFeB sintered magnets include using heavy rare earth elements Dy and Tb to replace Nd to improve its coercivity. One of the common methods is to add heavy rare earth elements such as Dy, Tb, Ho, etc. to the magnet by grain boundary diffusion, that is, to arrange heavy rare earth elements on the surface of the magnet, and to diffuse the heavy rare earth elements into the magnet by using the concentration difference between the surface and the interior of the magnet as the diffusion power. The NdFeB magnet prepared by grain boundary diffusion has excellent comprehensive magnetic properties and consumes a small amount of heavy rare earth. However, the reserves of heavy rare earths Dy and Tb are scarce, expensive, and will reduce the remanence of the magnet. Therefore, how to obtain a rare earth permanent magnet diffusion alloy with good consistency of remanence, coercivity and squareness while reducing the addition of heavy rare earth is a problem to be solved in this field.

[0004] At present, the research direction of magnets produced by grain boundary diffusion process is mostly focused on the diffusion depth of heavy rare earth elements. By increasing the diffusion depth, heavy rare earth elements can penetrate into the interior of the magnet, the diffusion efficiency can be improved, and the coercive force of the magnet can be improved. However, when the diffusion depth reaches a near limit, the difficulty of further increasing the diffusion depth increases significantly, and the effect of increasing the diffusion depth on performance improvement is not ideal. Based on the above problems, this application aims to explore new dimensions to improve the diffusion effect and solve the problem of limited improvement in diffusion performance, so as to obtain magnets with high remanence and high coercive force. Summary of the invention

[0005] In order to at least solve one or more of the technical problems mentioned above, the present application proposes solutions for improving the prior art in multiple aspects.

[0006] According to one aspect of the present application, the present application provides a NdFeB magnet, wherein the NdFeB magnet comprises R2T 14 B main phase grains and grain boundary phase, the main phase grains in the region of 0.1 to 100 μm from the magnet surface of the NdFeB magnet have a heavy rare earth shell, and the NdFeB magnet comprises the following components:

[0007] R: 28~32wt%

[0008] B: 0.85~0.94wt%

[0009] Co: 0.4~2wt%

[0010] Cu: 0.1~0.8wt%

[0011] Ga: 0.1~0.3wt%

[0012] Al: 0.05~0.5wt%

[0013] M1: 0.4-1.0wt%, wherein M1 is selected from one or two of the elements Ti, Zr, Nb, W, and V,

[0014] Fe: 63-69wt%;

[0015] Wherein, R is a rare earth element, and R includes at least PrNd and R H , R H A heavy rare earth element selected from one or both of Dy and Tb;

[0016] Wherein, the percentage of the area of ​​all grain boundary phases in the cross section of the NdFeB magnet within the region of 0.1 to 100 μm from the magnet surface to the total area of ​​the cross section is 5.2 to 7.5%.

[0017] According to one embodiment of the present application, the content of R is 29-32wt%, and the distribution of the grain boundary phase in the center of the magnet satisfies the following conditions: the area of ​​all grain boundary phases in the cross-section of the magnet in the center of the magnet accounts for 4.2-6.1% of the total area of ​​the cross-section.

[0018] According to one embodiment of the present application, M1 contains at least one of Ti and Zr.

[0019] According to one embodiment of the present application, the composition of the NdFeB magnet includes at least one of the following features:

[0020] b.Cu: 0.1-0.3wt%;

[0021] c.Ti: 0.15-0.3wt%;

[0022] d. Co: 0.7~1.5wt%

[0023] eR H :0.3~2wt%.

[0024] According to one embodiment of the present application, the grain boundary phase includes R6T 13 M1 phase, all R6T in the cross section of the NdFeB magnet within the region of 0.1 to 100 μm from the magnet surface 13 The percentage of the area of ​​the M1 phase to the total area of ​​the cross section is 5.2-6.0%.

[0025] According to one embodiment of the present application, the R6T 13 The distribution of the M1 phase in the center of the magnet satisfies the following conditions: the magnet has all R6T 13 The percentage of the area of ​​the M1 phase to the total area of ​​the cross section is 4.2-5.0%.

[0026] According to one embodiment of the present application, the heavy rare earth element content of the heavy rare earth shell in the region 0.1 to 100 μm away from the magnet surface is 1.0 to 4.5 at %.

[0027] According to another aspect of the present application, the present application provides a method for preparing a NdFeB magnet, which comprises:

[0028] 1) using a predetermined raw material alloy to form a quick-setting alloy sheet by a quick-setting process;

[0029] 2) crushing the quick-setting alloy flakes obtained in step 1) by hydrogen, adding additives and jet milling to obtain alloy powder, wherein the average particle size D50 of the alloy powder is 2 to 5 μm;

[0030] 3) pressing the alloy powder obtained in step 2) under magnetic field orientation, the magnetic field strength is 1.8-2.5T, and obtaining a compact;

[0031] 4) placing the compact obtained in step 3) into a sintering furnace and sintering it in a vacuum or inert atmosphere to finally obtain a NdFeB magnet substrate;

[0032] 5) coating the surface of the magnet substrate obtained in step 4) with a diffusion source containing a heavy rare earth element, and then tempering the NdFeB magnet to obtain a NdFeB magnet;

[0033] The tempering treatment process is a three-stage process: the first-stage tempering temperature is 870-970°C, the insulation time is 2-20h, the second-stage tempering temperature is 380-580°C, the insulation time is 1-10h, and the third-stage tempering temperature is 620-670°C, the insulation time is 1-10h.

[0034] According to one embodiment of the present application, in the step 5), the tempering treatment process is: the first stage tempering temperature is 870-940°C, the holding time is 2-10h, the second stage tempering temperature is 420-570°C, the holding time is 1-10h, and the third stage tempering temperature is 630-670°C, and the holding time is 1-6h.

[0035] According to one embodiment of the present application, in the step 5), the tempering treatment process includes: a quenching treatment between the second stage tempering and the third stage tempering, with a cooling rate of 5 to 10°C / min, cooling to 100 to 300°C.

[0036] According to one embodiment of the present application, in the step 4), the process parameters of the sintering treatment include: a sintering temperature of 1030 to 1120° C., and a sintering time of 1 to 10 hours, preferably 6 to 10 hours.

[0037] According to one embodiment of the present application, in the step 5), before the tempering treatment, the coated magnet substrate is subjected to a diffusion treatment.

[0038] According to one embodiment of the present application, the diffusion temperature of the diffusion treatment is 870-940° C. and the time is 4-20 hours.

[0039] The technical solution of the embodiment of the present application controls the lower B content and the higher content of high-melting-point metal elements such as Ti and Zr in the substrate, reasonably regulates the ratio of high-melting-point elements to Ga elements, and adjusts the addition ratio of Cu elements at the same time, thereby reducing the hindering effect of the high-melting-point element content on the diffusion of heavy rare earths by forming M1B compounds in the substrate, and increasing the area ratio of the grain boundary phase of the magnet obtained after diffusion treatment, thereby obtaining a NdFeB magnet with high remanence and high coercivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] By reading the detailed description below with reference to the accompanying drawings, the above and other purposes, features and advantages of the exemplary embodiments of the present application will become easy to understand. In the accompanying drawings, several embodiments of the present application are shown in an exemplary and non-limiting manner, and the same or corresponding reference numerals represent the same or corresponding parts, wherein:

[0041] Figure 1 A scanning electron microscope photograph of a cross section of the magnet of Example 1 of the present application at a distance of 0.1-100 μm from the magnet surface is shown.

[0042] Figure 2 The scanning electron microscope photograph of the cross section of the magnet of Comparative Example 1 of the present application at a distance of 0.1-100 μm from the magnet surface is shown.

[0043] Figure 3A scanning electron microscope photograph of a cross section of the central portion of the magnet of Example 1 of the present application is shown.

[0044] Figure 4 A scanning electron microscope photograph of a cross section of the central portion of the magnet of Comparative Example 1 of the present application is shown. DETAILED DESCRIPTION

[0045] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present application.

[0046] It should be understood that the terms "include" and "comprising" used in the specification and claims of the present application indicate the presence of described features, wholes, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, wholes, steps, operations, elements, components and / or collections thereof.

[0047] It should also be understood that the terms used in this application specification are only for the purpose of describing specific embodiments and are not intended to limit the present application. As used in this application specification and claims, unless the context clearly indicates otherwise, the singular forms of "a", "an" and "the" are intended to include plural forms. It should also be further understood that the term "and / or" used in this application specification and claims refers to any combination of one or more of the associated listed items and all possible combinations, and includes these combinations.

[0048] The specific implementation methods of the present application are described in detail below in conjunction with the accompanying drawings. Unless otherwise specified, the materials, reagents and equipment used in the examples of the present application are all obtained from conventional commercial channels.

[0049] Specifically, the present application provides a neodymium iron boron magnet, wherein the neodymium iron boron magnet comprises R2T 14 B main phase grains and grain boundary phase, the NdFeB magnet has an R2T in the region of 0.1 to 100 μm from the magnet surface. 14 The surface layer of the B main phase grain has a heavy rare earth shell layer, and the NdFeB magnet comprises the following components:

[0050] R: 28~32wt%

[0051] B: 0.85~0.94wt%

[0052] Co: 0.4~2wt%

[0053] Cu: 0.1~0.8wt%

[0054] Ga: 0.1~0.3wt%

[0055] Al: 0.05~0.5wt%

[0056] M1: 0.4-1.0wt%, wherein M1 is selected from one or two of the elements Ti, Zr, Nb, W, and V,

[0057] Fe: 63-69wt%;

[0058] Wherein, R is a rare earth element, and R includes at least PrNd and R H , R H A heavy rare earth element selected from one or both of Dy and Tb;

[0059] The percentage of the area of ​​all grain boundary phases in the cross section of the NdFeB magnet within the region of 0.1 to 100 μm from the magnet surface to the total area of ​​the cross section is 5.2 to 7.5%.

[0060] Exemplarily, the percentage of the area of ​​all grain boundary phases in the cross-section of the magnet within the region of 0.1 to 100 μm from the surface of the magnet to the total area of ​​the cross-section can be 5.2%, 5.8%, 6.0%, 6.2%, 6.5%, 6.6%, 6.7%, 6.8%, 6.9%, 7.0%, 7.1%, 7.2%, 7.3%, 7.4%, 7.5% or any value within the range composed of any of the above numerical values.

[0061] The technical solution of the embodiment of the present application is in a NdFeB magnet raw material system with low B addition, and the Ga element addition in the substrate is controlled at a low level. The present application adds high-content high-melting-point metal elements such as Ti and Zr. The addition of high-content high-melting-point metal elements is beneficial to grain refinement and improve the intrinsic coercivity of the magnet, but is not conducive to the improvement of the remanence of the magnet. At the same time, in the process of diffusing heavy rare earths, the remanence of the magnet will inevitably decrease further, and the high-melting-point metal elements will hinder the diffusion. However, the present application reasonably controls the relationship between the high-melting-point elements and the Ga element, adjusts the Cu element addition ratio, combines the diffusion and tempering processes, and accurately adjusts the grain boundary phase area ratio, the distribution of the grain boundary phase, and the element distribution in the grain boundary phase, thereby preparing a NdFeB magnet with high remanence and high coercivity.

[0062] In some embodiments, the content of R is 29-32 wt %. For example, the content of R can be 29.0 wt %, 29.5 wt %, 30.0 wt %, 30.5 wt %, 31.0 wt %, 31.5 wt %, 32.0 wt % or any value within the range formed by any of the above values.

[0063] In some embodiments, the distribution of the grain boundary phase in the center of the magnet satisfies the following condition: the percentage of the area of ​​all grain boundary phases in the cross section of the magnet in the center of the magnet to the total area of ​​the cross section is 4.2-6.1%. Exemplarily, the percentage of the area of ​​all grain boundary phases in the cross section of the magnet in the center of the magnet to the total area of ​​the cross section can be 4.2%, 4.5%, 5.0%, 5.2%, 5.3%, 5.4%, 5.5%, 5.6%, 5.7%, 5.8%, 5.9%, 6.0%, 6.1% or any value within the range formed by any of the above values.

[0064] In some embodiments, M1 contains at least one of Ti and Zr.

[0065] In some embodiments, the composition of the NdFeB magnet includes B: 0.85-0.94wt%. For example, the content of B can be 0.85wt%, 0.86wt%, 0.87wt%, 0.88wt%, 0.89wt%, 0.90wt%, 0.91wt%, 0.92wt%, 0.93wt%, 0.94wt% or any value within the range of any of the above values.

[0066] In some embodiments, the composition of the NdFeB magnet includes Cu: 0.1-0.3 wt %. For example, the content of Cu can be 0.10 wt %, 0.12 wt %, 0.15 wt %, 0.18 wt %, 0.20 wt %, 0.22 wt %, 0.25 wt %, 0.28 wt %, 0.30 wt % or any value within the range of any of the above values.

[0067] In some embodiments, the composition of the NdFeB magnet includes Ti: 0.15-0.3 wt %. For example, the content of Ti can be 0.15 wt %, 0.18 wt %, 0.20 wt %, 0.22 wt %, 0.25 wt %, 0.28 wt %, 0.30 wt % or any value within the range of any of the above values.

[0068] In some embodiments, the composition of the NdFeB magnet includes Co: 0.7-1.5 wt %. For example, the content of Co can be 0.7 wt %, 0.8 wt %, 0.9 wt %, 1.0 wt %, 1.1 wt %, 1.2 wt %, 1.3 wt %, 1.4 wt %, 1.5 wt % or any value within the range of any of the above values.

[0069] In some embodiments, the composition of the NdFeB magnet includes R H :0.3~2wt%R His a heavy rare earth element selected from one or both of Dy and Tb. H The content can be 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1.0wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt%, 1.5wt%, 1.6wt%, 1.7wt%, 1.8wt%, 1.9wt%, 2.0wt% or any value within the range composed of any of the above values.

[0070] In some embodiments, the atomic ratio of Al / Ga is 1.2 to 2, and the atomic ratio of Zr / Ga is 1.5 to 2. When Ga is within the above range, the intrinsic coercivity of the magnet can be reasonably increased while avoiding the cost increase caused by excessive addition.

[0071] In some embodiments, the grain boundary phase includes R6T 13 M1 phase, the R6T 13 The distribution of the M1 phase in the region of 0.1 to 100 μm from the magnet surface satisfies the following conditions: all R6T 13 The percentage of the area of ​​the M1 phase to the total area of ​​the cross section is 5.2-6.0%. For example, all R6T phases in the cross section within the region of 0.1-100 μm from the magnet surface are 13 The percentage of the area of ​​the M1 phase to the total area of ​​the cross section may be 5.2%, 5.3%, 5.4%, 5.5%, 5.6%, 5.7%, 5.8%, 5.9%, 6.0% or any value within the range formed by any of the above values.

[0072] The R6T 13 The M1 phase is shown as a gray grain boundary phase in the microstructure cross-section photograph, wherein the atomic percentage of the rare earth element R is 20% to 31%. 13 The M1 phase includes T element, the atomic percentage of T is 60% to 75%, the T element includes Fe and / or Co, and M is selected from one or more of Al, Cu, Ga, Ti, Sn, Zr, and Nb.

[0073] The center of the magnet refers to a region that is 500 μm or more away from the surface of the magnet.

[0074] In some embodiments, the R6T 13 The distribution of the M1 phase in the center of the magnet satisfies the following conditions: the magnet has all R6T 13 The percentage of the area of ​​the M1 phase to the total area of ​​the cross section is 4.2-5.0%.13 The percentage of the area of ​​the M1 phase to the total area of ​​the cross section may be 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5.0% or any value within the range formed by any of the above values.

[0075] In some embodiments, it is characterized in that R2T 14 The surface layer of the B main phase grain has a heavy rare earth shell layer, and the heavy rare earth element content of the heavy rare earth shell layer in the region 0.1 to 100 μm from the magnet surface is 1.0 to 4.5 at%. Exemplarily, the heavy rare earth element content of the heavy rare earth shell layer in the region 0.1 to 100 μm from the magnet surface can be 1.0 at%, 1.5 at%, 2.0 at%, 2.5 at%, 3.0 at%, 3.5 at%, 4.0 at%, 4.5 at%, or any value within the range formed by any of the above values.

[0076] The present application also provides a method for preparing a NdFeB magnet, which comprises:

[0077] 1) using a predetermined raw material alloy to form a quick-setting alloy sheet by a quick-setting process;

[0078] 2) crushing the quick-setting alloy flakes obtained in step 1) by hydrogen, adding additives and jet milling to obtain alloy powder, wherein the average particle size D50 of the alloy powder is 2 to 5 μm;

[0079] 3) pressing the alloy powder obtained in step 2) under magnetic field orientation, the magnetic field strength is 1.8-2.5T, and obtaining a compact;

[0080] 4) placing the compact obtained in step 3) into a sintering furnace and sintering it in a vacuum or inert atmosphere to finally obtain a NdFeB magnet substrate;

[0081] 5) coating the surface of the magnet substrate obtained in step 4) with a diffusion source containing a heavy rare earth element, and then tempering the NdFeB magnet to obtain a NdFeB magnet;

[0082] The tempering treatment process is a three-stage process: the first-stage tempering temperature is 870-970°C, the insulation time is 2-20h, the second-stage tempering temperature is 380-580°C, the insulation time is 1-10h, and the third-stage tempering temperature is 620-670°C, the insulation time is 1-10h.

[0083] According to the records of the prior art (CN111312463), when the B content in the substrate is lower than 0.95wt%, for example 0.84-0.94wt%, the high M1 element tends to form M1B compounds at the grain boundaries of the triangular region. During the diffusion of heavy rare earths, the M1B compounds hinder the diffusion of heavy rare earths and affect the diffusion depth.

[0084] After discovering the above problems, the inventors proposed a process to improve the area ratio of the grain boundary phase in the magnet, that is, no tempering is performed after sintering, and a three-stage tempering process is performed after coating with heavy rare earth, so as to accurately control the formation of the grain boundary phase in the magnet, and use the lower temperature of the second tempering and the higher temperature of the third tempering to allow the edges of the main phase grains to participate in the reaction, thereby promoting the consistency of the intercrystalline reaction inside the magnet. Finally, by adopting the above three-stage tempering process, more liquid phase is generated in the surface area (0.1-100μm) of the magnet, and more uniform R6T is generated. 13 M1 phase. At the same time, since part of the main phase participates in the reaction, it will also adjust the uniformity of the heavy rare earth shell of the magnet. A more uniform shell helps to improve the demagnetization consistency inside the magnet, thereby preparing a magnet with high remanence and high coercivity.

[0085] In some embodiments, in step 1), the composition ratio of the raw material alloy of the predetermined configuration is in accordance with the composition ratio of the NdFeB magnet substrate.

[0086] The composition ratio range of the NdFeB magnet substrate is:

[0087] Re: 28~32wt%

[0088] B: 0.85~0.94wt%

[0089] Co: 0.4~2wt%

[0090] Cu: 0.1~0.8wt%

[0091] Ga: 0.1~0.3wt%

[0092] Al: 0.05~0.5wt%

[0093] M1: 0.4-1.0wt%, wherein M1 is selected from one or two of the elements Ti, Zr, Nb, W, and V,

[0094] Fe: 63~69wt%.

[0095] In some embodiments, in step 5), the diffusion source containing heavy rare earth elements includes heavy rare earth compounds or heavy rare earth alloys. The heavy rare earth compounds are preferably fluorides and hydrides of heavy rare earths. The heavy rare earth alloys are preferably alloys of heavy rare earths and transition metals (such as Ti, Co, Ni) and low melting point metals (such as Al, Cu, Ga).

[0096] In some embodiments, in the three-stage tempering process, the temperature of the first stage tempering is 870-970°C, and the holding time is 2-20h. Preferably, the first stage tempering temperature is 870-940°C, and the holding time is 2-10h. Exemplarily, the temperature of the first stage tempering is 870°C, 880°C, 890°C, 900°C, 910°C, 920°C, 930°C, 940°C, or any value within the range of any of the above values. Exemplarily, the holding time of the first stage tempering is 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, 6h, 6.5h, 7h, 7.5h, 8h, 8.5h, 9h, 9.5h, 10h, or any value within the range of any of the above values.

[0097] In some embodiments, in the three-stage tempering process, the temperature of the second stage tempering is 380-580°C, and the holding time is 1-10h. Preferably, the second stage tempering temperature is 420-570°C, and the holding time is 2-10h. Exemplarily, the temperature of the second stage tempering is 420°C, 430°C, 440°C, 450°C, 460°C, 485°C, 500°C, 515°C, 535°C, 550°C, 570°C, or any value within the range of any of the above values. Exemplarily, the holding time of the second stage tempering is 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, 6h, 7h, 8h, 9h, 10h, or any value within the range of any of the above values.

[0098] In some embodiments, in the three-stage tempering process, the temperature of the third stage tempering is 620-670°C, and the holding time is 1-10 hours. Preferably, the temperature of the third stage tempering is 630-670°C, and the holding time is 1-6 hours. Exemplarily, the temperature of the third stage tempering is 630°C, 635°C, 640°C, 645°C, 650°C, 655°C, 660°C, 665°C, 670°C or any value within the range of any of the above values. Exemplarily, the holding time of the third stage tempering is 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, 6h or any value within the range of any of the above values.

[0099] In some embodiments, in the step 5), the tempering process includes: there is a quenching treatment between the second tempering and the third tempering, the cooling rate is 5-10°C / min, and the temperature is cooled to 100-300°C. Exemplarily, the cooling rate of the quenching treatment is 5°C / min, 5.5°C / min, 6°C / min, 6.5°C / min, 7°C / min, 7.5°C / min, 8°C / min, 8.5°C / min, 9°C / min, 9.5°C / min, 10°C / min or any value within the range of any of the above values. Exemplarily, the quenching treatment is cooled to 100°C, 120°C, 150°C, 180°C, 200°C, 220°C, 250°C, 280°C, 300°C or any value within the range of any of the above values.

[0100] In some embodiments, in the step 4), the process parameters of the sintering treatment include: a sintering temperature of 1030-1120°C, a time of 1-10 hours, preferably 6-10 hours. Exemplarily, the sintering temperature is 1030°C, 1040°C, 1050°C, 1060°C, 1070°C, 1080°C, 1090°C, 1100°C, 1110°C, 1120°C or any value within the range of any of the above values. Exemplarily, the sintering time is 6h, 6.5h, 7h, 7.5h, 8h, 8.5h, 9h, 9.5h, 10h or any value within the range of any of the above values. Specific embodiments

[0102] Example 1

[0103] Magnet substrate formula:

[0104]

[0105] 1) Casting quick-setting alloy sheets using a quick-setting process using the raw alloy prepared according to the above formula;

[0106] 2) hydrogen crushing and fine grinding are performed on the quick-setting alloy flakes obtained in step 1) to obtain raw alloy powder; wherein the hydrogen absorption pressure of hydrogen crushing is 0.3 MPa and the dehydrogenation temperature is 560° C.; the fine grinding is performed in a jet mill with a grinding pressure of 0.68 MPa; and the average particle size D50 of the raw alloy powder is 4 μm;

[0107] 3) pressing the raw alloy powder obtained in step 2) under magnetic field orientation, the magnetic field strength is 1.8T, and obtaining a compact;

[0108] 4) placing the compact obtained in step 3) into a sintering furnace and sintering the compact in a vacuum or inert atmosphere to obtain a NdFeB magnet substrate;

[0109] 5) The surface of the magnet substrate obtained in step 4) is coated with a diffusion source containing the heavy rare earth element Tb (specifically, the diffusion source is TbH2), and the coated NdFeB magnet substrate is tempered to obtain a NdFeB magnet.

[0110] The above tempering process adopts a three-stage tempering process:

[0111] The first-stage tempering temperature is 890°C, and the holding time is 4h; the second-stage tempering temperature is 500°C, and the holding time is 8h; the third-stage tempering temperature is 630°C, and the holding time is 5h.

[0112] Example 2

[0113] Magnet substrate formula:

[0114]

[0115] The difference from the preparation method of Example 1 is that in the three-stage tempering process, the first-stage tempering temperature is 870°C, the holding time is 6 hours, the second-stage tempering temperature is 430°C, the holding time is 9 hours, and the third-stage tempering temperature is 640°C, and the holding time is 5 hours; the other steps are the same as in Example 1.

[0116] Example 3

[0117] Magnet substrate formula:

[0118]

[0119] The difference from the preparation method of Example 1 is that

[0120] Step 5): The surface of the magnet substrate obtained in step 4) is coated with a diffusion source of dysprosium hydride, and the coated NdFeB magnet substrate is subjected to diffusion treatment at a diffusion temperature of 880° C. and a diffusion time of 6 hours; the magnet after diffusion treatment is subjected to a three-stage tempering treatment. The other steps are the same as those in Example 1.

[0121] In the three-stage tempering treatment process, the first-stage tempering temperature is 870°C, the holding time is 2h, the second-stage tempering temperature is 580°C, the holding time is 4h, and the third-stage tempering temperature is 640°C, the holding time is 5h.

[0122] Comparative Example 1

[0123] The only difference from Example 1 is the formula of the magnet substrate, and the other steps are the same as Example 1.

[0124] Magnet substrate formula:

[0125]

[0126] Comparative Example 2

[0127] The same magnet formula as in Example 1 is used, and the preparation steps except for the diffusion treatment / tempering treatment process are the same as in Example 1.

[0128] The only difference is that step 5) adopts conventional diffusion and tempering processes, with a diffusion temperature of 800° C., a diffusion time of 10 h, a tempering temperature of 550° C., and a tempering time of 8 h to obtain a NdFeB magnet.

[0129] The test methods used in this application are as follows:

[0130] Microstructure test method:

[0131] A scanning electron microscope test is performed on any 10 or more cross sections of the magnet perpendicular to the diffusion direction, and the area of ​​all grain boundary phases in each cross section is counted to calculate the percentage of the area of ​​all grain boundary phases in each cross section to the total area of ​​the cross section. Then, the average value of the percentage of all cross sections is calculated as the percentage of the area of ​​all grain boundary phases in the cross section of the NdFeB magnet to the total area of ​​the cross section. The size of the observation area is, for example, 40μm×40μm and 75μm×75μm; the magnification is 2000 to 5000 times.

[0132] According to a similar method, the percentage of the area of ​​all grain boundary phases in the cross section of the magnet within the region of 0.1 to 100 μm from the magnet surface to the total area of ​​the cross section, the percentage of all R6T phases in the cross section of the magnet within the region of 0.1 to 100 μm from the magnet surface, and the percentage of the area of ​​all R6T phases in the cross section of the magnet within the region of 0.1 to 100 μm from the magnet surface can also be obtained. 13 The percentage of the area of ​​the M1 phase to the total area of ​​the cross section, the percentage of the area of ​​all grain boundary phases in the cross section of the magnet in the center of the magnet to the total area of ​​the cross section, the percentage of the area of ​​all R6T phases in the cross section of the magnet in the center of the magnet 13 The percentage of the area of ​​the M1 phase to the total area of ​​the cross section, etc. Figure 1-Figure 4 As shown, the grain boundary phase in the triangle area marked by ○ is R6T 13 M1 phase.

[0133] EDS energy spectrum analysis is used to test the atomic percentage of each element in the grain boundary phase of NdFeB magnets to obtain element data at each depth of the magnet.

[0134] The test sample size is 35.5*26*3.6mm, and the test is carried out using a pulse hysteresis loop measuring instrument.

[0135] The magnetic properties test data of Example 1 and Comparative Example 1 are as follows:

[0136]

[0137] The microstructure test results of Example 1 and Comparative Example 1 are as follows:

[0138] Embodiment 1:

[0139] According to the experimental data of Example 1, the area of ​​all grain boundary phases in the cross section of the magnet within the region of 0.1 to 100 μm from the magnet surface accounts for 6.75% of the total area of ​​the cross section; the area of ​​all R6T phases in the cross section of the magnet within the region of 0.1 to 100 μm from the magnet surface accounts for 6.75% of the total area of ​​the cross section. 13 The percentage of the area of ​​the M1 phase to the total area of ​​the cross section is 5.5%.

[0140] The percentage of the area of ​​all grain boundary phases in the cross section of the magnet at the center of the magnet to the total area of ​​the cross section is 5.4%; the percentage of all R6T in the cross section of the magnet at the center of the magnet to the total area of ​​the cross section is 5.4%. 13 The percentage of the area of ​​the M1 phase to the total area of ​​the cross section is 4.37%.

[0141] Comparative Example 1:

[0142] According to the experimental data of Comparative Example 1, the area of ​​all grain boundary phases in the cross section of the magnet within the region of 0.1 to 100 μm from the magnet surface accounts for 5.1% of the total area of ​​the cross section; the area of ​​all R6T phases in the cross section of the magnet within the region of 0.1 to 100 μm from the magnet surface accounts for 5.1% of the total area of ​​the cross section. 13 The percentage of the area of ​​the M1 phase to the total area of ​​the cross section was 5.0%.

[0143] The percentage of the area of ​​all grain boundary phases in the cross section of the magnet at the center of the magnet to the total area of ​​the cross section is 4.0%; the percentage of the area of ​​all R6T phases in the cross section of the magnet at the center of the magnet to the total area of ​​the cross section is 4.0%. 13 The percentage of the area of ​​the M1 phase to the total area of ​​the cross section was 4.1%.

[0144] As described above, the magnet substrate formula of Comparative Example 1 is different from that of Example 1. In the magnet substrate ratio of Comparative Example 1, the Ga content is 0.31wt%, the Zr content is 0.1wt%, and no element Ti is contained; that is, the content of high melting point metal elements (Zr and Ti, etc.) in Comparative Example 1 is much less than that in the embodiment of the present application, while the Ga content is slightly higher than that in the embodiment of the present application. In the case of this magnet substrate ratio, even if the same three-stage tempering process as in Example 1 is used, all grain boundary phases or all R6T in the cross section within the region of 0.1 to 100 μm from the magnet surface in the magnet of Comparative Example 1 are 13 The area proportion of the M1 phase is significantly smaller than that of Example 1 of the present application. At the same time, in the cross section of the magnet in the center of the magnet of Comparative Example 1, all the grain boundary phases or all the R6T 13 The area proportion of the M1 phase is also significantly smaller than the corresponding proportion in Example 1 of the present application.

[0145] Correspondingly, the magnetic properties of the magnet of Comparative Example 1 are also significantly reduced. The coercive force of the magnet of Comparative Example 1 is 24.52 kOe, which is significantly lower than the coercive force of 26.49 kOe of the magnet of Example 1. The squareness of the magnet of Comparative Example 1 is 97.9%, which is significantly lower than the squareness of 99.6% of the magnet of Example 1.

[0146] Comparative Example 2 uses the same magnet formula as Example 1, but step 5) of Comparative Example 2 uses a conventional diffusion and tempering process; in this case, the magnetic properties of the magnet of Comparative Example 2 are also significantly reduced. The coercive force of the magnet of Comparative Example 2 is 21.97 kOe, which is much lower than the coercive force of 26.49 kOe of the magnet of Example 1, and the squareness of the magnet of Comparative Example 2 is 97.3%, which is significantly lower than the squareness of 99.6% of the magnet of Example 1.

[0147] Although multiple embodiments of the present application have been shown and described herein, it is obvious to those skilled in the art that such embodiments are provided only by way of example. Those skilled in the art can think of many changes, modifications and alternatives without departing from the thought and spirit of the present application. It should be understood that in the process of practicing the present application, various alternatives to the embodiments of the present application described herein can be adopted. The attached claims are intended to limit the scope of protection of the present application, and therefore cover equivalents or alternatives within the scope of these claims.

Claims

1. A neodymium iron boron magnet, characterized in that: The NdFeB magnet includes R2T 14 B main phase grains and grain boundary phase, The R2T of the NdFeB magnet within the region of 0.1 to 100 μm from the magnet surface 14 The surface layer of the B main phase grain has a heavy rare earth shell layer, and the NdFeB magnet comprises the following components: R: 28~32wt% B: 0.85~0.94wt% Co: 0.4~2wt% Cu: 0.1~0.8wt% Ga: 0.1~0.3wt% Al: 0.05~0.5wt% M1: 0.4-1.0wt%, wherein M1 is selected from one or two of the elements Ti, Zr, Nb, W, and V, Fe: 63-69wt%; Wherein, R is a rare earth element, and R includes at least PrNd and R H , R H R is a heavy rare earth element. H One or two selected from Dy and Tb; Wherein, the area of ​​all grain boundary phases in the cross section of the NdFeB magnet within a region of 0.1 to 100 μm from the magnet surface accounts for 5.2 to 7.5% of the total area of ​​the cross section.

2. The NdFeB magnet according to claim 1, characterized in that: The content of R is 29-32wt%, and the distribution of the grain boundary phase in the center of the magnet meets the following conditions: the percentage of the area of ​​all grain boundary phases in the cross section of the magnet in the center of the magnet to the total area of ​​the cross section is 4.2-6.1%.

3. The NdFeB magnet according to claim 1, characterized in that: M1 contains at least one of Ti and Zr.

4. The NdFeB magnet according to any one of claims 1 to 3, characterized in that: The composition of the NdFeB magnet includes at least one of the following features: a.Cu: 0.1~0.3wt%; b.Ti: 0.15-0.3wt%; c. Co: 0.7~1.5wt% d.R H :0.3~2wt%。 5. The NdFeB magnet according to any one of claims 1 to 3, characterized in that: The grain boundary phase includes R6T 13 M1 phase, all R6T in the cross section of the NdFeB magnet within the region of 0.1 to 100 μm from the magnet surface 13 The percentage of the area of ​​the M1 phase to the total area of ​​the cross section is 5.2-6.0%.

6. The NdFeB magnet according to any one of claims 1 to 3, characterized in that: The R6T 13 The distribution of the M1 phase in the center of the magnet satisfies the following conditions: the magnet has all R6T 13 The percentage of the area of ​​the M1 phase to the total area of ​​the cross section is 4.2-5.0%.

7. The NdFeB magnet according to any one of claims 1 to 3, characterized in that: The content of heavy rare earth elements in the heavy rare earth shell layer in the area 0.1 to 100 μm away from the magnet surface is 1.0 to 4.5 at %.

8. A method for preparing a neodymium iron boron magnet, characterized in that: include: 1) using a predetermined raw material alloy to form a quick-setting alloy sheet by a quick-setting process; 2) crushing the quick-setting alloy flakes obtained in step 1) by hydrogen, adding additives and jet milling to obtain alloy powder, wherein the average particle size D50 of the alloy powder is 2 to 5 μm; 3) pressing the alloy powder obtained in step 2) under magnetic field orientation, the magnetic field strength is 1.8-2.5T, and obtaining a compact; 4) placing the compact obtained in step 3) into a sintering furnace and sintering it in a vacuum or inert atmosphere to finally obtain a NdFeB magnet substrate; 5) coating the surface of the magnet substrate obtained in step 4) with a diffusion source containing a heavy rare earth element, and then tempering the NdFeB magnet to obtain a NdFeB magnet; The tempering treatment process is a three-stage process: the first-stage tempering temperature is 870-970°C, the insulation time is 2-20h, the second-stage tempering temperature is 380-580°C, the insulation time is 1-10h, and the third-stage tempering temperature is 620-670°C, the insulation time is 1-10h.

9. The preparation method according to claim 8, characterized in that: In the step 5), the tempering treatment process is: the first stage tempering temperature is 870-940°C, the holding time is 2-10h, the second stage tempering temperature is 420-570°C, the holding time is 1-10h, and the third stage tempering temperature is 630-670°C, and the holding time is 1-6h.

10. The preparation method according to claim 9, characterized in that: In the step 5), the tempering process includes: a quenching treatment between the second stage tempering and the third stage tempering, with a cooling rate of 5 to 10°C / min, cooling to 100 to 300°C.

Citation Information

Patent Citations

  • R-t-b-based permanent magnet and method for manufacturing same

    CN113614864A

  • Neodymium-iron-boron magnet material and preparation method thereof

    CN115020057A

  • Sintered neodymium-iron-boron permanent magnet and preparation method and application thereof

    CN115240944A

  • Sintered neodymium-iron-boron magnet and preparation method thereof

    CN115798853A

  • High-performance sintered neodymium-iron-boron magnet and preparation method

    CN117912784A

Cited By

  • Neodymium-iron-boron magnet, magnet matrix and preparation method of neodymium-iron-boron magnet

    CN120126887A